Komparasi Paradigma Kepemimpinan Kiai Tradisional dan Modern dalam Manajemen Lembaga Pendidikan Islam - Ashari, Hasim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2021)
Pesantren in Indonesia is diverse, there is a model of pesantren salaf, classic, or traditional. There is also a modern boarding school. And there is also a comprehensive pesantren, which is a pesantren that combines salaf curriculum with government curriculum. Pesantren salaf or modern pesantren can not be separated from the paradigm and model of Kiai leadership. . Kiai dipesantren has a strong influence. Kiai's decision cannot be contested by anyone, including how to manage the pesantren. Today, pesantren has grown rapidly. The existence of pesantren in Indonesia became the main foundation of deradicalization and filtering of liberal understanding through global flows. This article describes leadership facts. Traditional and Modern Kiai and its implications for the management of Islamic Educational Institutions. The research method used is qualitative research with the type of literature study research. From the results of the analysis obtained conclusions as a result: Paradgima Kiai has implications for the management system of Islamic Educational Institutions. Pesantren with a classical or traditional management system is generally motivated by the Kiai paradigm. While pesantren with modern management system is also motivated by paradgima kiai. Traditional boarding schools lead to institutions that are committed to shutting themselves off from changes in the education system. It is better understood as an orthodox, static, closed, and traditional institution. While modern Pesantren is a development of classical pesantren. Facilities, facilities, and infrastructure are more complete. Generally the modern pesantren curriculum is compiled from the results of the integration of the pesantren curriculum with the government curriculum, the two provisions of the curriculum are squeezed into one unit